2003
DOI: 10.1889/1.1832379
|View full text |Cite
|
Sign up to set email alerts
|

15.1: Emissive Microdisplay using Light Emitting Polymer

Abstract: An emissive microdisplay technology has been developed which incorporates a layer of light emitting polymer on a CMOS substrate. Monochrome microdisplays of QVGA (320 × 240) resolution have been manufactured and early aspects of their initial characterization are presented. Benefits of the technology include very low power consumption plus relatively simple drive electronics and opto‐mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The circuit shown in Figure 8 has been implemented in a microdisplay backplane that has been used successfully in two prototype microdisplays -the ME3201 monochrome QVGA microdisplay [9] and the ME1602 color QQVGA microdisplay [10]. In the case of ME1602, the 320x240 individual pixel circuits are grouped into 160x120 color pixels where each color pixel has 4 sub-pixels in a 2x2 format.…”
Section: Digital Pcm Pixel Circuit Implementationmentioning
confidence: 99%
“…The circuit shown in Figure 8 has been implemented in a microdisplay backplane that has been used successfully in two prototype microdisplays -the ME3201 monochrome QVGA microdisplay [9] and the ME1602 color QQVGA microdisplay [10]. In the case of ME1602, the 320x240 individual pixel circuits are grouped into 160x120 color pixels where each color pixel has 4 sub-pixels in a 2x2 format.…”
Section: Digital Pcm Pixel Circuit Implementationmentioning
confidence: 99%
“…They report that the CMOS backplane used to drive the LEP is the same one reported by Blalock et al 63 as a backplane for a ferroelectric LC microdisplay. In 2003, Bodammer et al 64 reported a QVGA monochrome active matrix backplane used in conjunction with a green emitter and a white emitter. This leads us to the conclusion that grayscale was achieved by pulse width modulation and the LEP was driven in constant voltage mode.…”
Section: Polymer Oled Microdisplaysmentioning
confidence: 99%
“…We have previously described a QVGA monochrome microdisplay [5] and a QQVGA color microdisplay [6] utilizing LEP on CMOS technology.…”
Section: Lep Microdisplay Technologymentioning
confidence: 99%